Dragon Fruit Peels Waste as Cosmetic: An Overview - Fatimi, Hana Anisa; Ramadhana, Irma Hazira Awalinda; Purnama, Magnifico Fatta (Jurnal FARMASIMED (JFM), 2025)
Dragon fruit peels (Hylocereus polyrhizus) have various potential as a base ingredient in eco-friendly cosmetic products. This study focused on evaluating the bioactive properties of dragon fruit peels, finding that the compounds contained therein are more effective in counteracting free radicals than the flesh of the fruit. Data collection techniques were carried out by literature study and digital information search with the target objectives in the form of literature study (literature review) searching for information from relevant literature sources for two week in November - December 2024 by searching >30 references from Google Scholar, ResearchgateNet and Sciencedirect, Sinta, MDPI, Pubmed. As well as, official websites in the range of 2014-2024. Literature study was conducted by identifying problems regarding the content of different formulations. The method was through a qualitative approach, which is descriptive research and tends to use analysis. Dragon fruit peel extract showed significant activity in preventing skin damage caused by UV rays and pollution. This innovation not only provides a solution for agro-industrial waste reduction, but also creates sustainable cosmetic products with high economic value. This waste utilization supports the consumer trend towards products based on natural and environmentally friendly ingredients From this review, dragon fruit peels have a great opportunity to be used as an active ingredient in various types of cosmetic products, such as moisturizers, serums, creams, and face masks, with a positive impact on skin health and the environment.